THE ROLE OF HUMAN RESOURCES COMPETENCY MODERATING THE EFFECT OF TEAMWORK AND EMPLOYEE ENGAGEMENT ON THE PERFORMANCE OF SUB-DISTRICT OFFICE EMPLOYEES AT KOTA TERNATE - Ruslan Sukardi Djauhar; Abdul Hadi Sirat; Abdullah W. Jabid (Jurnal Ekonomi, 2023)
Ruslan S. DJauhar (2023).The Role of Human Resource Competence in Moderating Teamwork and Employee Involvement in the Performance of Employee at District Office at Kota Ternate. Chairman of the Advisory Commission: Abdul Hadi Sirat, Member: Abdullah W. Jabid.The purpose of this study was to see the effect of teamwork, employee involvement on employee performance, and the role of human resource competence in moderating teamwork and employee involvement on employee performance.This study adopted a quantitative methodology, collecting data through questionnaires, and obtaining responses from respondents (n = 97) from 97 respondents who had work experience in their fields. The measurement model and hypothesis testing were carried out using the Smart PLS software.The results of the study show that teamwork and employee involvement have a positive effect on employee performance, and human resource competence strengthens the influence of teamwork and employee involvement on employee performance.Teamwork and employee involvement in employee performance can be enhanced by the role of human resource competence. In order to realize the effectiveness of employee performance needs to be evaluated regularly to avoid problems arising in employee performance. It is hoped that future research will add to the survey method apart from distributing questionnaires/questionnaires as well as conducting interviews to obtain additional information so that accurate results will be obtained to improve employee performance.